2020
DOI: 10.2139/ssrn.3764589
|View full text |Cite
|
Sign up to set email alerts
|

Technology, Labour Market Institutions and Early Retirement: Evidence from Finland

Abstract: There are two major barriers to increasing employment of older workers. First, older workers engaged in codifiable, routine tasks are particularly prone to the risk of being displaced by computers and robots. Second, several countries have in place various labour market institutions that encourage early retirement, such as exceptional entitlements or looser criteria for unemployment and disability benefits applied to older individuals. We present evidence that these two factors reinforce each other to push old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…When unemployment is the dependent variable, the main and interaction effects of robot exposure fail to reach statistical significance, which should be remarked as a limitation to our study. Even if industrial robots affect employment outcomes in the manufacturing sector directly, these changes are not necessarily reflected in equivalent changes in unemployment, since the workers displaced by industrial robots have other transition options such as retraining or (early) retirement (Yashiro et al, 2020).…”
Section: Robustness Checksmentioning
confidence: 99%
See 1 more Smart Citation
“…When unemployment is the dependent variable, the main and interaction effects of robot exposure fail to reach statistical significance, which should be remarked as a limitation to our study. Even if industrial robots affect employment outcomes in the manufacturing sector directly, these changes are not necessarily reflected in equivalent changes in unemployment, since the workers displaced by industrial robots have other transition options such as retraining or (early) retirement (Yashiro et al, 2020).…”
Section: Robustness Checksmentioning
confidence: 99%
“…For instance, Dauth et al (2021: 3127–3128) find that robot-exposed manufacturing workers are twice as likely to remain with their original employer in German regions with stronger unionization. In Finland, automation-exposed workers have a higher likelihood of early retirement, which might be interpreted as another channel of protecting workers from technological unemployment (Ebbinghaus, 2001; Yashiro et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Older workers could, therefore, experience more situations with technologically-related stress arising from dependency on, e.g., information and communication technologies at work, which could induce stress and exhaustion [ 11 , 12 ]. Furthermore, a recent report employing data from Finland revealed that an individual aged 50 or above in occupations that are more exposed to digital technologies has a higher probability of exiting employment each year [ 13 ].…”
Section: Introductionmentioning
confidence: 99%